The Sinful Church and Its Need for Constant Conversion - Slunitschek, Agnes (The ecumenical review, 2024)
This article justifies and demonstrates that the church, and not only its members, is capable of sinning. It can thereby become a structure of sin and be called a sinful church. This is exemplified through the cases of the Roman Catholic Church's handling of sexual abuse and the Residential School System in Canada. This highlights that the churches, along with calling the world, societies, and all people to change where it is needed, should also be constantly self-examining and self-correcting.